John the Baptist, Jesus and the Parable of the Tares - Catchpole, David R. (Scottish journal of theology, 1978)
The parable of the Tares is introduced by Matthew into the third of the major discourses he attributes to Jesus, a discourse for which he relies heavily on both Mark 4 and Q (Matt. 13.16f = Luke 10.23f; Matt. 13.31f 33 = Luke 13.18f, 20f). While lacking any full parallel in either of these sources, the parable does recall in varying ways several other synoptic traditions, (i) The Markan parable of the Seed growing Secretly/Patient Husbandman (Mark 4.26–29) occupied in the Markan sequence the position now occupied in the Matthaean scheme by the parable of the Tares. Moreover, the occurrence of verbal reminiscences of the former in the latter has not infrequently impressed interpreters: anthrōpos, katheudein, sītos, blastanein, chortos, karpos, therismos, prōton. While some of these might be attributable to correspondences natural in the coverage of similar subject-matter, not all of them are necessary to such coverage (e.g. katheudein), not all of them are common words (e.g. blastanein), and the aggregate of all of them cannot easily be written off as coincidence, (ii) The parable of the Sower, with its appended interpretation (Mark 4.3–8, 14–20 = Matt. 13.3–8, 18–23), provides a precedent within this discourse for an explanation based on a series of 1:1 allegorical correspondences (see particularly, in the case of the Tares, vv. 37–39, which provide the basis for a summarising explanation in vv. 40–43: hōsper…).